Coupled Mg/Ca and Clumped Isotope Measurements Indicate Lack of Substantial Mixed Layer Cooling in the Western Pacific Warm Pool During the Last ∼5 Million Years. Issue 8 (4th August 2021) - Meinicke, N.; Reimi, M. A.; Ravelo, A. C.; Meckler, A. N.
Abstract: The Indo‐Pacific Warm Pool (IPWP) plays a crucial role in influencing climate dynamics both in the tropics and globally. Yet, there is an ongoing controversy concerning the evolution of surface temperatures in the IPWP since the Pliocene, which is fueled by contradictory proxy evidence. Temperature reconstructions using TEX86 indicate a gradual cooling by ∼2°C from the Pliocene to today while Mg/Ca‐based studies using planktonic foraminifera do not report any long‐term trends. A bias in Mg/Ca records due to seawater chemistry changes has been suggested as an explanation for this proxy mismatch. Here, we present data from two independent foraminifera‐based temperature proxies, Mg/Ca and clumped isotopes (Δ47 ), measured on the same samples from IODP Site U1488 in the IPWP. We reconstructed mixed layer and subsurface temperatures and find very good agreement among Mg/Ca and Δ47 when applying a minor correction for changing Mg/Ca ratios of seawater. Diagenetic effects could influence Δ47 but the evaluation of foraminifera preservation at Site U1488 suggests that this effect is unlikely to have masked a long‐term trend in the data. While remaining uncertainties prevent us from fully ruling out particular hypotheses, our study adds evidence that mixed layer temperatures likely did not cool substantially, while subsurface temperatures cooled more strongly since the Pliocene. The substantial Pleistocene cooling previously observed in TEX86 data is consistent with this finding when interpreting it as a combined surface and subsurface signal. Plain Language Summary: Although the Indo‐Pacific Warm Pool (IPWP) is a major player within the global climate system, our understanding of sea surface temperatures in the Indo‐Pacific Warm Pool (IPWP) since the Pliocene (5.3–2.6 Million years ago) is limited. Various methods to reconstruct past ocean temperatures disagree on the long‐term temperature evolution in this region. Studies using the TEX86 paleothermometer indicate a ∼2°C surface ocean cooling while the Mg/Ca‐based temperature reconstructions lack a clear long‐term trend since the Pliocene. Different sources of uncertainty can potentially explain this mismatch, including ocean chemistry changes influencing Mg/Ca or differences in the water depth represented by the different proxy signals. Here, we present data from two independent geochemical methods (Mg/Ca and clumped isotopes: Δ47 ), using the shells of two species of marine microplankton called foraminifera, representing two different water depths. Reconstructing surface and subsurface ocean temperatures in the IPWP we find good agreement between both methods when correcting the Mg/Ca data for minor ocean chemistry changes. While uncertainties remain, our data argue against a substantially warmer Pliocene surface ocean but show a marked cooling of subsurface temperatures. The clear difference between surface and subsurface evolution can reconcile previous proxy data if they represent different water depths. Key Points: Combined clumped isotope and Mg/Ca measurements validate previously published Mg/Ca‐based studies from the Plio‐Pleistocene Indo‐Pacific No substantial cooling of the mixed layer in the Western Pacific Warm Pool during the last ∼5 Myrs while the subsurface cooled from 4 Ma on Only a minor correction for Mg/Casw changes is needed for the last ∼5 Myrs